Pelaksanaan Upaya Hukum PDAM Surya Sembada Atas Pelanggaran Kontrak Berlangganan Air Oleh Konsumen - Sanjaya, Guntur Rapi; Suharto, Miko Aditiya (HUKMY : Jurnal Hukum, 2024)
This research aims to understand the concept of implementing water subscription contracts between the Regional Water Company (PDAM) and Consumers in PDAM Surya Sembada, Surabaya City. The study is motivated by issues of contract violations that occur after consumers subscribe to water services with PDAM Surya Sembada, Surabaya City. The research methodology employed is juridical empirical with a case study approach focusing on instances at PDAM Surya Sembada, Surabaya City. Legal resources include primary, secondary, and non-legal sources. Data were collected through field studies and literature reviews at the Enforcement Division office, PDAM Surya Sembada, Surabaya City. Findings reveal that in the 2023 period, there were 290 cases of water subscription contract violations, comprising 104 cases of default and 186 cases of unlawful conduct by consumers. Resolution of violations occurred without litigation but through non litigious approaches in accordance with the company's operational standards, referencing the Surabaya City Mayor Regulation No. 29 of 2011 regarding the Management and Provision of Drinking Water by the Regional Water Company Surya Sembada, incorporated into the water subscription contract by the company.